The Issue of ’In Itself’: A Logical and Fundamentalist Comparative Study - Aboaladas, Ibrahem Ahmad (Dirasat: Shari’a and Law Sciences, 2025)
Objectives: This study aims to explore the concept of “the matter” as understood by philosophers, focusing on their doctrines and methods for proving its truth. It examines the relationship between these philosophies and contemporary thought, along with their effects on the origins and branches of religion. Methods: The study employs a transmission approach to present relevant texts, an inductive approach to trace and collect information from approved sources, and an analytical approach to compare, analyze, and discuss the texts. Results: The study concludes that, according to most religious scholars, the concept of “the matter” in the context of religiou s fundamentals refers to the essence of what God Almighty has decreed, which is Islam. In the branches of jurisprudence, the “same matter” pertains to the responsibility of the accountable person to fulfill what God has prescribed at certain times, as interpreted by the diligent individual. The study also demonstrates that the formulation of the concept of “knowledge” by fundamentalists aligns with the scholars’ understanding of the essence of the same matter in both its principles and branches. Conclusion: The study highlights the excellence of Muslims in formulating logical terms, including the distinctions they made in relation to the subject. It concludes by showing how philosophical terms were adjusted to fit legal standards. The study recommends further discussion on philosophical terms and emphasizes the ability of Muslims to refine them.